CONVERGENCE OF MARKETING AND FINANCIAL AND ECONOMIC SECURITY IN THE CONDITIONS OF DIGITAL TRANSFORMATION - LIUBOKHYNETS, Larysa; POPLAVSKA, Olga; VINSKEVYCH, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the relationship between marketing and financial and economic security in the context of the development of information technologies, as their convergence is an integral part of modern business. Digital transformations significantly change the landscape of marketing and financial and economic security, in order to work successfully in new conditions, enterprises must invest in digital technologies, protect customer data and systems from cyber attacks and fraudulent actions, constantly adapt to new technologies and market conditions. In today's conditions, economy, rationality and maximum efficiency based on the use of modern information and multimedia technologies are a guarantee not only of quality management, but also of the company's overall competitiveness in the markets.Marketing plays a key role in ensuring the financial and economic security of the enterprise, i.e. constant monitoring of the market, analysis of competitors and study of customer needs allow timely detection of potential threats and development of effective strategies to neutralize them. Thanks to a deep understanding of customer needs and market dynamics, marketing contributes to the development of effective strategies that allow the enterprise to adapt to changes and maintain its competitiveness, optimize its costs, improve product quality and strengthen its position in the market. In the conditions of growing global competition, companies must understand the development trends of international markets, cultural characteristics and take into account legislative norms in their activities. In this case, marketing helps to adapt business to new conditions, and economic security provides protection from external threats. The rapid development of digital technologies is changing the rules of the game in the market, while marketing allows effective use of digital channels to interact with customers, and economic security provides protection against cyber threats and other risks related to digital technologies. Consumers increasingly expect a personalized approach and high quality products and services, so marketing helps to understand the needs of customers and develop appropriate offers, and financial and economic security ensures that these offers will be fulfilled with quality and time. New players are constantly entering the market, which complicates competition, so there is a need to stand out among competitors, determine the company's competitive advantages, build a positive image and effectively manage crisis situations. In this case, economic security protects against unfair competition, ensures business stability in conditions of uncertainty, helps protect company data from cyber attacks and fraudulent actions, and prevents financial losses.Therefore, ensuring financial and economic security during marketing operations is a complex task that requires a complex approach. The convergence of marketing and financial and economic security allows you to minimize risks, ensure sustainable business development and effective promotion of goods and services, and protect the reputation of the company and its assets. The interaction of marketing and economic security helps prevent crisis situations related to security breaches that can negatively affect the company's image, as well as avoid ineffective spending on marketing campaigns related to unsafe or unethical practices
Keywords: convergence; marketing; financial and economic security; economic security; margin of safety; methods of situational management; method of sensitivity analysis; risk sensitivity coefficient; fraud; indicators of functional components of economic security